A case of myopericytoma causing radial artery aneurysm - Mohamad Chehab, MD; Jonathan Kanakaraj, MD; Francisco C. Albuquerque, Jr., MD; Robert A. Larson, MD; Mark M. Levy, MD; Daniel H. Newton, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
A 44-year-old male without history of infection, catheterization, or instrumentation of his left upper extremity presented with a slow-growing pulsatile mass of his forearm. Ultrasound and magnetic resonance imaging revealed a large radial artery aneurysm. Because of worsening paresthesia and pain in his hand, the patient underwent surgical excision of the aneurysm. Pathology revealed an extremely rare case of completely intravascular myopericytoma, originating from the radial artery wall and causing large aneurysmal dilation. Postoperatively, the patient had no vascular or sensorimotor deficits. We suggest that arterial wall myopericytoma can be managed with surgical excision for tissue diagnosis and symptomatic relief.